Clinical Observation on the Therapeutic Effect of Port-Wine Stains with Intravenous Injection of Hematoporphyrin Monomethyl Ether (HMME) - Ning J; Wang F; Liu SQ; Zhang RZ; Liu DM; Li Y (Dove Medical Press, 2024)
Jing Ning,1 Fang Wang,1 Shui-Qing Liu,2 Ru-Zhi Zhang,3 Dan-Min Liu,1 Yan Li1 1Department of Dermatology, The Third Affiliated Hospital of Soochow University, Changzhou, Jiangsu, People's Republic of China; 2Department of Ultrasound in Medicine, The Third Affiliated Hospital of Soochow University, Changzhou, Jiangsu, People's Republic of China; 3Department of Dermatology, The Second Affiliated Hospital of Wannan Medical College, Wuhu, Anhui, 240000, People's Republic of ChinaCorrespondence: Ru-Zhi Zhang, Email zhangruzhi628@163.comBackground: Hematoporphyrin monomethyl ether (HMME) is a promising photosensitizer for photodynamic therapy (PDT) and has found wide application in the treatment of port-wine stains (PWS).Objective: This study aims to observe and analyze the clinical efficacy and safety of HMME-PDT in the treatment of PWS patients. It also aims to evaluate the usefulness of color Doppler flow imaging (CDFI), an ultrasound technique for detecting blood flow in skin lesions, in assessing clinical efficacy.Methods: Thirty-three patients with PWS underwent HMME-PDT at our dermatology outpatient clinic between January 2019 and March 2020. Data on patient demographics, lesion location, lesion type (pink, purple, nodular thickening), treatment frequency, and pre- and post-treatment images were collected and retrospectively analyzed. CDFI was performed on three patients.Results: All patients received intravenous HMME and underwent irradiation with 532 nm green LED light. Of these, 5 patients received 1 session of HMME-PDT, 14 received 2 sessions, 9 received 3 sessions and the remaining 5 patients received more than 3 sessions. Of the 33 patients, 9 were cured (27.27%), 10 showed improvement (30.30%), 11 experienced a reduction in symptoms (33.33%), and 3 showed no significant improvement (9.09%). Most patients reported local pain and oedema, and no systemic adverse effects were observed. Clinical efficacy correlated with lesion type and total number of treatment sessions. CDFI appears to be an excellent technique for assessing clinical efficacy.Conclusion: HMME-PDT is a safe and effective method for the treatment of PWS. CDFI examination appears to be a promising assessment tool. However, further validation with larger sample sizes is warranted.Keywords: port-wine stains, hematoporphyrin monomethyl ether, photodynamic therapy, color Doppler flow imaging